A modeling study to define guidelines for antigen screening in schools and workplaces to mitigate COVID-19 outbreaks - Jeong, YD; Ejima, K; Kim, KS; Iwanami, S; Hart, WS; Thompson, RN; Jung, IH; Iwami, S; Aihara, K (Springer Nature, 2025)
Background In-person interaction offers invaluable benefits to people. To guarantee safe in-person activities during a COVID-19 outbreak, effective identification of infectious individuals is essential. In this study, we aim to analyze the impact of screening with antigen tests in schools and workplaces on identifying COVID-19 infections.